Preparation and Controlled Release Properties of Probiotic Hydrogel Carrier Based on Citrus Cellulose - Shaoyang WANG; Ziyuan LI; Lina QIN; Xinyi CHEN; Liqi WANG; Tiemin JIANG; Haiyun LI (Shipin gongye ke-ji)
To enhance the survival rate and release rate of probiotics in gastrointestinal fluids, hydrogels were prepared using citrus cellulose and sodium carboxymethylcellulose as embedding materials, with citric acid as the cross-linking agent. Lactiplantibacillus plantarum B5 was adsorbed and embedded in the hydrogels to evaluate the embedding rate, controlled release performance, bile salt tolerance, and storage stability. Results demonstrated that hydrogels with varying ratios exhibited favorable embedding effects, with an embedding rate exceeding 79%. The hydrogel with a citrus cellulose to sodium carboxymethylcellulose ratio of 1:4 showed optimal controlled release performance, achieving a release rate of 89.25% in simulated intestinal fluid. The bacteriophage-carrying hydrogel significantly enhanced the survival rate of L. plantarum B5 in bile salt solution, reaching 87.09%. The hydrogel maintained a storage stability of 30 days at 4 ℃, with the survival rate of embedded L. plantarum B5 exceeding 60% after 30 days, particularly reaching 70.66% with the 1:4 ratio of citrus cellulose to sodium carboxymethylcellulose, and maintaining viable bacteria levels above 7 lg CFU/mL. Studies have shown that citrus cellulose-sodium carboxymethylcellulose hydrogels are effective in reducing the exposure of probiotics to unfavorable factors in the external environment, thus significantly improving their survival in various environments.